Peningkatan Kreativitas Dan Hasil Belajar Siswa Kelas V Pada Pembelajaran Matematika Model Problem Based Learning Di Sd 37/Iii Koto Tuo Kecamatan Depati Vii Kabupaten Kerinci - Nia Amelia (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The low of learning out come and student creativity at SDN 37 / III Koto Tuo is caused by conventional teaching method. This reasearch is puposed to describe to increase creativity and results of student learning at V grade in mathematic learning by using problem based learning model at SDN 37/III Koto Tuo. The design of this research is model classroom actoin research. The subject of this research is V grade which amounts to 17 student. The instrument that is used observasion et teacher activity, observasion sheet creativity of student learning. The result showed that the student creativity obtained an average persentage of that in the first cycle of 50,73% ( show in the table 2 page 55) , cycle to 70,95% (show in the table 6, page 70). Besides that the average of student’s, learning out come in the first cycle 67,08 (show in page 54) has been increased in the second cycle 77,18 (show in page 70), the improvement of cycle I to cycle II at 10,1. Based on data analysis it can be conclude that the using of problem based learning model can enhance the creativity and student learning out comes in V grade in mathematic learning at SDN 37/III Koto Tuo Dpati VII subistrict, Kerinci regence.